Dark Energy Survey Year 1 results: weak lensing mass calibration of redMaPPer galaxy clusters. Issue 1 (8th October 2018) - McClintock, T; Varga, T N; Gruen, D; Rozo, E; Rykoff, E S; Shin, T; Melchior, P; DeRose, J; Seitz, S; Dietrich, J P; Sheldon, E; Zhang, Y; et al.
ABSTRACT: We constrain the mass–richness scaling relation of redMaPPer galaxy clusters identified in the Dark Energy Survey Year 1 data using weak gravitational lensing. We split clusters into 4 × 3 bins of richness λ and redshift z for λ ≥ 20 and 0.2 ≤ z ≤ 0.65 and measure the mean masses of these bins using their stacked weak lensing signal. By modelling the scaling relation as 〈 M 200m |λ, z 〉 = M 0 (λ/40) F ((1 + z )/1.35) G, we constrain the normalization of the scaling relation at the 5.0 per cent level, finding M 0 = [3.081 ± 0.075(stat) ± 0.133(sys)] · 10 14 M⊙ at λ = 40 and z = 0.35. The recovered richness scaling index is F = 1.356 ± 0.051 (stat) ± 0.008 (sys) and the redshift scaling index G = −0.30 ± 0.30 (stat) ± 0.06 (sys). These are the tightest measurements of the normalization and richness scaling index made to date from a weak lensing experiment. We use a semi-analytic covariance matrix to characterize the statistical errors in the recovered weak lensing profiles. Our analysis accounts for the following sources of systematic error: shear and photometric redshift errors, cluster miscentring, cluster member dilution of the source sample, systematic uncertainties in the modelling of the halo–mass correlation function, halo triaxiality, and projection effects. We discuss prospects for reducing our systematic error budget, which dominates the uncertainty on M 0 . Our result is in excellent agreement with, but has significantly smaller uncertainties than, previous measurements in the literature, and augurs well for the power of the DES cluster survey as a tool for precision cosmology and upcoming galaxy surveys such as LSST, Euclid, and WFIRST.